PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN(STUDI PADA BAKPIA KARTINI) - Supriyana; Bayu, Niswan (Fakultas Ekonomi Universitas Gresik, 2021)
The increasingly fierce business competition, especially competition from similar companies, makes companies increasingly demanded to move faster in terms of attracting consumers. So that companies that apply the concept of marketing need to pay attention to consumer behavior and the factors that influence their purchasing decisions in marketing efforts of a product. This is because in the concept, one way to achieve company goals is to know what the needs and wants of consumers or target markets are and provide the expected satisfaction more effectively and efficiently than competitors. The type of research used in compiling this research is to use explanatory or explanatory or explanatory research. Explanatory research explains the cause of an event. For this reason, it is necessary to identify various variables outside the problem to confirm the cause of a problem. This research is quantitative using data from MSME Bakpia Kartini Gresik which consists of three hundred (300) consumer data with a sample of one hundred and seventy one (171) consumers where the results of the survey can determine the effect of price and product quality on product purchasing decisions in Indonesia. Bakpia Kartini Gresik.